Financial Inclusion through Islamic Microfinance: Empirical Evidence from Developing Countries - Syahrul Hidayat, Muhammad; Mazidah, Nurul; Setia Aksana, Didik Supardana; Nurhayati, (International Journal of Scientific Research and Management (IJSRM), 2023)
This study explores the important role played by Islamic microfinance in promoting financial inclusion in developing countries. Using empirical evidence, this research shows how Islamic microfinance institutions have helped in reducing poverty and improving the economic welfare of underprivileged communities. Through secondary data analysis and case studies, this research highlights how sharia economic principles such as the prohibition of riba (interest) and the emphasis on asset-based contracts have facilitated access to financial services for individuals previously underserved by conventional financial institutions. This research also discusses the challenges faced by the Islamic microfinance sector and provides recommendations for the future